2013
DOI: 10.2512/jspm.8.177
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sodium bisulphate on the stability of octreotide acetate: compatibility study with dexamethasone injection

Abstract: Background: Although several dexamethasone phosphate preparations are commercially available and frequently administered with octreotide acetate, their compatibility remains unknown. Aim: We investigated the effect of pH and sodium bisulphate on the stability of octreotide acetate. Measurement design: Octreotide acetate percentage was measured 3 and 10 days after it was mixed with 2 dexamethasone phosphate preparations containing different concentrations of sodium bisulphate as an additive, and in one that did… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…A significant decrease was observed in the concentration of OCT on day 0, and this has been attributed to the progression of hydrolysis at the time of the measurement due to sample preparation time. Further decreases may occur in OCT concentration depending on other factors, such as the pH, temperature and exposure to light; 9 19 therefore, mixing should be avoided under these conditions. Judgements regarding expiry dates (from immediately after preparation to the completion of its use) are varied when the final SBS concentration is 0.1 mg/mL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant decrease was observed in the concentration of OCT on day 0, and this has been attributed to the progression of hydrolysis at the time of the measurement due to sample preparation time. Further decreases may occur in OCT concentration depending on other factors, such as the pH, temperature and exposure to light; 9 19 therefore, mixing should be avoided under these conditions. Judgements regarding expiry dates (from immediately after preparation to the completion of its use) are varied when the final SBS concentration is 0.1 mg/mL.…”
Section: Discussionmentioning
confidence: 99%
“…6–8 We previously investigated incompatibilities with dexamethasone (DEX) injections, which are sold as an ethical drug, and demonstrated that OCT concentrations were maintained for 10 days in a mixture with a DEX injection that did not contain SBS but were significantly decreased in a mixture with a SBS-containing DEX injection. 9 However, the concentrations of SBS that have a clinical influence have not yet been determined, and the stability of these drugs, other than DEX, remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…However, diŠerent additives have been reported to aŠect the stability of injections between original injections and generic injections. 5,6) In addition, far less information is provided for generic injections than for original injections. In hospitals, therefore, clinical pharmacists often use the data from the original injections when using generic injections.…”
Section: Introductionmentioning
confidence: 99%
“…Asahara et al 20) reported that insulin was easily degraded by disulphide bond cleavage in the presence of SBS. Although octreotide also contains a disulfide bond, Tanabe et al 21) reported that degradation of octreotide was mainly due to hydrolysis not to cleavage of the disulphide bond in the molecule. Our results confirm this conclusion and show that octreotide seems to be easily hydrolysed.…”
Section: Sbs 1 Totalmentioning
confidence: 99%